만성폐쇄성폐질환 및 미세먼지 유발 폐손상 동물모델에서 과루행련환의 효과 - 이철화; 양원경; 유이란; 김승형; 박양춘; Lee, Chul-wha; Yang, Won-kyung; Lyu, Yee-ran; Kim, Seung-hyeong; Park, Yang-chun (대한한방내과학회지, 2017)
Objective: This study aimed to use a mouse model to evaluate the effects of Gwaruhaengryeon-hwan (GHH) on chronic obstructive pulmonary disease (COPD) and particulate matter induced lung injury. Materials and Methods: The study was carried out in two ways (in vitro, in vivo). In vitro RAW 264.7 cells (mouse macrophage) were used and analyzed by flow cytometry, ELISA. In vivo lipopolysaccharide (LPS) and cigarette smoke solution (CSS), or coal, fly ash, diesel exhaust particle (CFD) challenged mice were used and its BALF was analyzed by ELISA, lung tissue by real-time PCR. Results: In vitro, GHH maintained an 80-100% rate of viability. So cytotoxicity was not shown. In the ELISA analysis with RAW 264.7 cells, GHH significantly decreased NO over $30μg/ml$. In the ELISA analysis, GHH significantly decreased $TNF-α$, IL-6 over $300μg/ml$. In the COPD model, the GHH 200 mg/kg dosage group, the application of GHH significantly decreased the increasing of neutrophils, $TNF-α$, IL-17A, MIP2, CXCL-1 in BALF, $TNF-α$, $IL-1β$ mRNA expression in lung tissue and histological lung injury. In the CFD induced lung injury model, the GHH 200 mg/kg dosage group, the application of GHH significantly decreased the increase of neutrophils, $TNF-α$, IL-17A, MIP2, CXCL-1 in BALF, MUC5AC, $TGF-β$ mRNA expression in lung tissue and histological lung injury. Conclusion: This study suggests the usability of GHH for COPD patients by controlling lung tissue injury.